Business Cycle Synchronization in Latin American. A Critical Survey of Empirical Research - Díaz Kovalenko, Igor Ernesto; Barros Naranjo, Jhon Ronald; Barrera Rea, María Gabriela; Barros Naranjo, Robert Gustavo (Migration Letters, 2023)
This paper develops a systematic literature review to show the state of the art in business cycle research in Latin America by analyzing articles that use a variety of data and approaches to measure the business cycle and convergence. Thus, this research focuses on two questions: whether business cycles become more similar over time and what factors drive business cycle synchronization. We conclude that business cycles in the Latin American region have gone through periods of both convergence and divergence, but that in general, evidence of a common business cycle in the region is limited. The level of synchronization varies across countries and sub-regions, and there are significant differences in the behavior of economies during recessions and expansions. Trade plays a crucial role in the propagation of the cycle, but the strength of synchronization between individual countries and the United States is unclear. In addition, the region’s dependence on external events, particularly since the 2008 global recession, and the dominance of trade flows over financial flows are highlighted as determinants of business cycle comovements in the short term. Studies also suggest that Latin America’s disconnection from advanced economies may be influenced by increased trade with China and the low degree of financial integration with its main partners.